Versatile vectors to study recoding: conservation of rules between yeast and mammalian cells. - Stahl, G (1995)
In many viruses and transposons, expression of some genes requires alternative reading of the genetic code, also called recoding. Such events depend on specific mRNA sequences and can lead to read through of an in-frame stop codon or to +1 or -1 frameshifting. Here, we addressed the issue of conservation of recoding rules between the yeast Saccharomyces cerevisiae and mammalian cells by establishing a versatile vector that can be used to study recoding in both species. We first assessed this vector by analysing the site of +1 frameshift of the Ty1 transposon. Two sequences from higher organisms were then tested in both yeast and mammalian cells: the gag-pol junction of human immunodeficiency virus type 1 (HIV-1) (a site of -1 frameshift), and the stop codon region of the replicase cistron from the tobacco mosaic virus (a site of UAG read through). We show that both sequences direct a high level of recoding in yeast. Furthermore, different mutations of the target sequences have similar effects on recoding in yeast and in mouse cells. Most notably, a strong decrease of frameshifting was observed in the absence of the HIV-1 stem-loop stimulatory signal. Taken together, these data suggest that mechanisms of some recoding events are conserved between lower and higher eukaryotes, thus allowing the use of S. cerevisiae as a model system to study recoding on target sequences from higher organisms.